Estimation and valuation in accounting - Ionescu, Cicilia; Georgescu, Floarea (Journal of Economic Development, Environment and People, 2014)
The relationships of the enterprise with the external environment give rise to a range of informational needs. Satisfying those needs requires the production of coherent, comparable, relevant and reliable information included into the individual or consolidated financial statements. International Financial Reporting Standards IAS / IFRS aim to ensure the comparability and relevance of the accounting information, providing, among other things, details about the issue of accounting estimates and changes in accounting estimates. Valuation is a process continually used, in order to assign values to the elements that are to be recognised in the financial statements. Most of the times, the values reflected in the books are clear, they are recorded in the contracts with third parties, in the supporting documents, etc. However, the uncertainties in which a reporting entity operates determines that, sometimes, the assigned or values attributable to some items composing the financial statements be determined by use estimates.